The birds of New Jersey : status and distribution - Boyle, William J. (Princeton University Press, 2011)
New Jersey provides some of the most varied and exciting birding in North America, and more than 450 species have been recorded in the state. Yet there has been no comprehensive and readily available guide to the status and distribution of all these species--until now. The Birds of New Jersey is the most up-to-date and succinct guide for the birds of New Jersey and includes all species known to the state from historical times to the present. Featuring over 200 color photos of rarities and regular species, this book authoritatively provides individual entries that include a summary of status an.